Presence of phthalates in toys analysed by Institute of Public helath “Dr Milan Jovanović Batutt” for a last five years period (2017-2021) - Milenković, Milan; Erceg, Milica; Blagojević, Zorica; Djukić-Ćosić, Danijela; Antonijević, Biljana; Bulat, Zorica (Archives of Pharmacy, 2022)
Phthalates are commonly used plasticizers for plastic materials. Number of toys are made from plastic materials or are coated with plastic layer. No existence of chemical bound between phthalates and polymer layers means their easy migration. Children’s exposure to phthalates is recognised as a threat to their health, since phthalates interfere with hormones level (endocrine disrupter chemicals – EDC), but can also induce hepatotoxicity, renal toxicity, allergic diseases and astma and disrupt thyroid function. Rulebook on Toy safety (“Official Gazette of RS” No. 78/2019) was published in 2019, to set rules on toys safety and their free movement on the market. Phthalates are prohibited, individually or in combination in a concentration equal to or greater than 0.1% (m/m). Butylbenzyl phthalate (BBP), Di-n-butyl phthalate (DBP), Bis(2-ethylhexyl) phthalate (DEHP) and Diisobutyl phthalate (DIBP) are listed as prohibited, but DIBP restrictions start from July 2023. In accordance with this legislative, laboratory of Institute of Public Health of Serbia “Dr Milan Jovanovic Batut” analyses part of these toys present on the market in Serbia. Total of 232 toy samples were analysed in the last 5 years (2017-2021), by HPLC-DAD. Phthalates are found in 40 samples (17.2%), 10 samples (4.3%) were bellow and 30 (12.9%) exceeded concentration of 0.1% (m/m). The most common elevated phthalates were DEHP and DBP. During 2019 and 2021 no phthalates are found in samples. Constant appearance of new toy manufacturers and control of existing ones demand monitoring of toys present on RS market, for the purpose of children's safety.